Linking intraspecific variability in trophic and functional niches along an environmental gradient. (20th April 2020) - Raffard, Allan; Santoul, Frédéric; Blanchet, Simon; Cucherousset, Julien
Abstract: Intraspecific trophic variability has important ecological and evolutionary implications, and is driven by multiple interacting factors. Functional traits and environmental conditions are important in mediating the trophic niche of individuals because they determine their ability to consume certain prey, their energetic requirements, and resource availability. In this study, we aimed at investigating the interacting effects of functional traits and environmental conditions on several attributes of trophic niche in natural populations. Here, we quantified intraspecific variability in the trophic niche of 12 riverine populations of European minnow ( Phoxinus phoxinus ) using stable isotope analyses. Functional traits (i.e. morpho‐anatomical traits) and environmental conditions (i.e. upstream–downstream gradient, forest cover) were quantified to identify the determinants of (1) trophic position and resource origin, (2) trophic niche size, and (3) trophic differentiation (β‐diversity) among populations. We demonstrated that trophic position and resource origin covaried with functional traits related to body size and locomotion performance, and that the strength and shape of these relationships varied according to local environmental conditions. The trophic niche size also differed among populations, although no determinant was identified. Finally, trophic β‐diversity was correlated to environmental differentiation among sites. Overall, the determinants of intraspecific variability in trophic niche appeared highly context‐dependent, and related to the interactions between functional traits and environmental conditions. Because populations are currently facing important environmental changes, understanding this context‐dependency is important for predicting food web structure and ecosystem dynamics in a changing world.